2016
DOI: 10.1002/mnfr.201500775
|View full text |Cite
|
Sign up to set email alerts
|

Gut barrier impairment by high‐fat diet in mice depends on housing conditions

Abstract: We demonstrated that housing conditions and associated changes in gut bacterial colonization are pivotal for maintenance of gut barrier integrity in DIO mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 39 publications
6
38
0
Order By: Relevance
“…As expected, housing conditions markedly influenced the composition of the microbiota in mice (this study and reviewed in [39]) and intestinal barrier integrity in mice fed a HFD [40]. Future studies should consider environmental conditions to be one of the most important factors affecting the composition of the mouse gut microbiome.…”
Section: Discussionsupporting
confidence: 54%
“…As expected, housing conditions markedly influenced the composition of the microbiota in mice (this study and reviewed in [39]) and intestinal barrier integrity in mice fed a HFD [40]. Future studies should consider environmental conditions to be one of the most important factors affecting the composition of the mouse gut microbiome.…”
Section: Discussionsupporting
confidence: 54%
“…The metabolic endotoxaemia hypothesis, which states that high dietary fat intake impairs the gut barrier, is largely based on data from dietary interventions studies in mice that received 78% of their daily calorie intake as fat in an essentially carbohydrate-free diet formulation 154 . Follow-up studies have shown that the proposed effect of HFD consumption on gut barrier integrity largely depends on housing conditions and bacterial colonization of the gut 155,156 .…”
Section: Dio-sensitive Sprague Dawleymentioning
confidence: 99%
“…The recently established catalogue of the mouse gut metagenome shows that the environment, determined by mouse provider and housing laboratory, has a more pronounced effect on the conventional gut microbiota than seen for mouse strain, feed or gender (Xiao et al, 2015). Environmental reprogramming of microbiota by breeding mice in a new site (Ussar et al, 2015) or altering housing conditions (Müller et al, 2015) is shown to change the development of the metabolic syndrome. However, the extent of microbial spread within a specific environment and the effects of this spread on the development of metabolic phenotypes have currently not been studied.…”
Section: Introductionmentioning
confidence: 99%